Evaluating Gene Fusions as Prognostic Biomarkers and Therapeutic Targets in Immune Checkpoint Blockade–Treated Advanced Melanoma: A Retrospective Analysis - Nibeyro, Guadalupe (2025)
Advanced melanoma, characterized by its aggressiveness and genomic complexity, demands improved prognostic and therapeutic strategies, particularly for patients with limited response to immune checkpoint blockade (ICB). Gene fusions, proposed as enhancers of tumor immunogenicity through neoantigens, also reflect chromosomal instability, which influences tumor evolution and therapy outcomes. However, their impact on melanoma remains unexplored. By retrospectively analyzing baseline tumors from 222 ICB-treated patients, we found a high tumor fusion burden (TFB-H) correlation with poor RECIST response, reduced overall survival (time-dependent ROC > 0.6, P << 0.01), and increased mortality risk (HR = 2, P < 0.01). TFB-H was found to be strongly associated with chromosomal instability (β = 0.72, P < 0.01), heightened proliferation, and diminished immune cytolytic activity. TFB-H was also linked to poor prognosis and immune impairment in nonadvanced melanoma tumors (n = 441) that have not received ICB treatment. These findings suggest that TFB-H tumors may exhibit an aggressive phenotype insensitive to ICB, probably due to immune evasion caused by intratumoral heterogeneity. Additionally, we identified targetable fusions, such as KIAA1549::BRAF, which represent therapeutic opportunities for advanced melanoma, including novel type II RAF inhibitors with potent activity against kinase fusions. Integrating gene fusion profiling into clinical practice may guide precision medicine strategies to overcome the limitations of ICB in advanced melanoma, offering prognostic insights and expanding therapeutic options, particularly with emerging fusion-specific inhibitors.Significance:The evidence of this work supports the idea that gene fusion profiling may serve as both a prognostic marker and a guide for alternative therapeutic strategies, including targeted fusion inhibitors, in patients less likely to benefit from ICB.